B-Bridge Regulated Asymmetric Dual-Atomic Catalysts for Synergistically Enhanced Styrene Mineralization and CO2 Reduction - Zhang, Xiai; Xu, Zhongshuang; Zhang, Xinwei; Wang, Jingquan; Liu, Dan; Miao, Huanran; Wang, Tong; Yang, Zhimao; Fan, Qikui; Kong, Chuncai (Nano-Micro Letters, 2025)
Developing innovative resource utilization strategies to achieve sustainable recycling of waste-to-fuel is highly desirable, yet the design of cost-effective bifunctional catalysts with dual high-efficiency remains unexplored. While the Fenton-like reaction relies on enhancing peroxymonosulfate (PMS) adsorption and accelerating interfacial electron transfer to improve kinetic rates, CO2 reduction is constrained by sluggish kinetics and competing hydrogen evolution reaction. Herein, we construct a bifunctional catalyst (NiFe-BNC) featuring dual-atomic active sites by introducing boron atoms into a biomass-derived chitosan substrate rich in functional groups, which optimizes atomic coordination environments. In situ experiments and density functional theory calculations reveal that B-atom modulation facilitates carbon substrate defect enrichment, while the charge-tuning effect between metal sites and "boron electron bridge" optimizes PMS adsorption configurations. This synergistic effect facilitates the interfacial electron transfer and enhances the CO2 adsorption capacity of NiFe-BNC by 6 times that of NiFe-NC. The obtained NiFe-BNC exhibits significantly enhanced catalytic activity and selectivity, realizing 99% efficient degradation of volatile organic pollutants in the flowing phase within 2 h and stable mineralization exceeding 60%, while achieving a large current density of 1000 mA cm−2 and CO Faraday efficiency of 98% in the flow electrolytic cell. This work innovatively paves a new way for the rational design of cost-effective functional catalysts to achieve carbon cycle utilization. Highlights: 1 Bifunctional atomic catalyst for dual environmental-energetic applications. 2 Unprecedented catalytic performance: simultaneously 99% flowing-phase styrene degradation and 98% FECO at 1000 mA cm−2. 3 Boron incorporation for accelerated electron transfer and optimized eCO2RR microenvironments.